2023
DOI: 10.3390/app13084674
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Scale Production of Single Cell Oil by Apiotrichum brassicae and Pichia kudriavzevii from Acetic Acid and Propionic Acid

Abstract: Volatile fatty acids can be used as a cheap carbon source for biotechnological lipid production with oleaginous yeasts, but one factor limiting their large-scale use is their inherent cytotoxicity. Developing a suitable cultivation strategy can help mitigate the adverse effect volatile fatty acids have, since these effects are strongly dependent on concentration and pH. This work shows that, by employing a pH-stat fed-batch approach for the cultivation of Apiotrichum brassicae V134 and Pichia kudriavzevii V194… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Cianchetta et al [ 16 ] concluded that linoleic acid and stearic acid are among the most important fatty acid constituents of the unicellular oil produced from Cutaneotrichosporon oleaginosum , Rhodosporidiobolus azoricus , and Lipomyces starkeyi . Khaleel and Fakhri [ 60 ] obtained SCO with high linoleic acid and stearic acid content, while Burgstaller et al [ 61 ] noted that the main fatty acid present in the oils produced from Apiotrichum brassicae and Pichia kudriavzevii was oleic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Cianchetta et al [ 16 ] concluded that linoleic acid and stearic acid are among the most important fatty acid constituents of the unicellular oil produced from Cutaneotrichosporon oleaginosum , Rhodosporidiobolus azoricus , and Lipomyces starkeyi . Khaleel and Fakhri [ 60 ] obtained SCO with high linoleic acid and stearic acid content, while Burgstaller et al [ 61 ] noted that the main fatty acid present in the oils produced from Apiotrichum brassicae and Pichia kudriavzevii was oleic acid.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the YC2 group displayed reduced Apiotrichum relative abundance when compared to CON group. The Apiotrichum has lipolytic activity (Burgstaller et al 2023 ), and the decreased Apiotrichum relative abundance may protect lipid from degradation in the rumen and can be used in the small intestine. Furthermore, obvious differences of unclassified_p__Ascomycota , Microascus , Ascochyta , Vishniacozyma , Neosetophoma and Sterigmatomyces relative abundances were observed among different treatments.…”
Section: Discussionmentioning
confidence: 99%